被災地沿岸部児童の身体活動および環境とその関連： 震災1年後と4年後の比較 - Okazaki, Kanzo; Suzuki, Koya; Sakamoto, Yuzuru; Sasaki, Keji (Hatsuiku hattatsu kenkyuu, 2017)
The purpose of this study was to examine levels of physical activity and its correlation with neighborhood environment among children living in the 2011 Great Eastern Japan Earthquake and Tsunami affected area. A serial cross-sectional data set was developed for this study by conducting two surveys at approximately 1 year (N=209) and 4 years (N=142) after the occurrence of the earthquake and tsunami. At each survey point, assessment of physical activity for fourth- through sixth-grade schoolchildren was performed using a self-administered questionnaire. The questionnaire also included questions on sex, age, grade, height, and weight. An independent t-test showed that the average sitting time on a weekday at the 4-year survey point was lower than that at the 1-year survey-point (t (296) =3.9, p<0.001, effect size (d) =0.22) . Analysis using the quantification theory type I revealed that neighborhood environment variables were not significantly associated with sitting time at the 4-year survey point. However, at the 1-year survey point, presence of sidewalks and residential density were significantly associated with sitting time on weekdays (β=−0.18, 95% confidence interval [CI] : −0.21 to −0.01, p=0.03) and sitting time on weekdays (β=−0.28, 95% CI:−0.27 to −0.08, p<0.001) and weekends (β=−0.20, 95% CI:−0.22 to −0.02, p=0.02) , respectively. Moreover, a binary logistic analysis showed that high intensity physical activity such as exercise and sport, was not associated with the neighborhood environment variables at the 4-year survey point, whereas access to recreational facilities (odds ratio=2.74, 95% CI:1.24 to 6.02, p=0.01) significantly correlated with exercise and sports at the 1-year survey point. These results suggest that environmental restoration possibly improved physical activity among the children.